Accuracy of methods to measure femoral head penetration within metal‐backed acetabular components. Issue 5 (12th July 2016) - Callary, Stuart A.; Solomon, Lucian B.; Holubowycz, Oksana T.; Campbell, David G.; Howie, Donald W.
ABSTRACT: A number of different software programs are used to investigate the in vivo wear of polyethylene bearings in total hip arthroplasty. With wear rates below 0.1 mm/year now commonly being reported for highly cross‐linked polyethylene (XLPE) components, it is important to identify the accuracy of the methods used to measure such small movements. The aims of this study were to compare the accuracy of current software programs used to measure two‐dimensional (2D) femoral head penetration (FHP) and to determine whether the accuracy is influenced by larger femoral heads or by different methods of representing the acetabular component within radiostereometric analysis (RSA). A hip phantom was used to compare known movements of the femoral head within a metal‐backed acetabular component to FHP measured radiographically using RSA, Hip Analysis Suite (HAS), PolyWare, Ein Bild Roentgen Analyse (EBRA), and Roentgen Monographic Analysis Tool (ROMAN). RSA was significantly more accurate than the HAS, PolyWare, and ROMAN methods when measuring 2D FHP with a 28 mm femoral head. Femoral head size influenced the accuracy of HAS and ROMAN 2D FHP measurements, EBRA proximal measurements, and RSA measurements in the proximal and anterior direction. The use of different acetabular reference segments did not influence accuracy of RSA measurements. The superior accuracy and reduced variability of RSA wear measurements allow much smaller cohorts to be used in RSA clinical wear studies than those utilizing other software programs. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:988–996, 2017. Abstract : Radiostereometric analysis (RSA) was significantly more accurate than the Hip Analysis Suite (HAS), PolyWare, and ROMAN methods when measuring 2D FHP with a 28 mm femoral head. Femoral head size influenced the accuracy of HAS and ROMAN 2D measurements, EBRA proximal measurements, and RSA proximal and anterior measurements. Different acetabular reference segments did not influence accuracy of RSA measurements. The superior accuracy and reduced variability of RSA measurements allow much smaller cohorts to be used in RSA clinical wear studies.